THE EMERGENCE AND EVOLUTION OF APPROACHES TO THE CATEGORY "ECONOMIC SECURITY OF THE STATE" (Marketing Journal, 2025)
This article scientifically analyzes the formation of the category of "economic security of the state", the emergence of theoretical approaches to it and the stages of its 385 evolution. In the initial period, the concept of economic security was associated with macroeconomic stability and national interests, but later it became a broad category such as socio -economic equality, territorial stability, resilience to external econo mic factors, and institutional development. The article comparatively studies the views of representatives of the classical economic school, modern institutional economists, and international organizations, and highlights the directions of conceptual devel opment of the theory of economic security. The results of the study justify the need to define economic security as a priority area of national policy and harmonize it with international experience.
Keywords: State economic security; theoretical approaches; evolution; national interest; macroeconomic stability; external economic threats; institutional development; international experience